Analisis Risiko Kesehatan Pajanan Debu Respirabel Pasca Instalasi Dust Supression System di Industri Pengolahan Bijih Mineral - Susanto, Arif; Hidayah, Nurulia; Budi, Savitri Citra; Setyana, Lilik Dwi (Universitas Hang Tuah Pekanbaru, 2025)
This study aimed to assess the health risks associated with respirable dust exposure following the implementation of a dust suppression system. A cross-sectional quantitative design was employed, involving 30 workers from PTX’s based on NIOSH. Personal dust sampling was conducted using the NMAM0600 method. The results indicated that the average concentration of respirable dust was 0.4760mg/m³, below the threshold limit value (TLV) of 3 mg/m³ set by the ACGIH. Risk characterization using the risk quotient (RQ), RQ<1. Simulation using the MPPD model revealed that particles with a diameter of approximately 4 µm had the highest deposition rate in the thoracic region of the respiratory tract, potentially triggering inflammatory responses and pulmonary fibrosis. Despite the low current exposure levels, continuous monitoring and enhancement of dust control measures are recommended to prevent long-term health effects such as silicosis and COPD. The study emphasizes the importance of regular health surveillance, appropriate use of personal protective equipment, and adherence to the ALARA (As Low As Reasonably Achievable) principle to ensure occupational safety and health in mineral ore processing environments.